Coronary Artery Disease in Patients with Diabetic Kidney Disease: Challenges and Contemporary Revascularization Strategies - Mahmoud Abdelaziz Abdelrashid, Ahmed Shafie Ammar, Abdulrahman Abdullah Abdulrahman Ibrahim*, Shimaa Gamal Zien El Abdeen (Cuestiones de Fisioterapia, 2024)
Background: Coronary artery disease (CAD) is the leading cause of morbidity and mortality among patients with diabetic kidney disease (DKD). The coexistence of diabetes mellitus and chronic kidney dysfunction accelerates atherosclerosis through complex metabolic, inflammatory, and vascular mechanisms, resulting in more extensive coronary involvement and poorer cardiovascular outcomes than those observed in the general population